FRI0294 The Accuracy of Osteoporotic Fracture Risk Prediction Tools: A Systematic Review and Meta-Analysis. (9th June 2015) - Marques, A.A.; Ferreira, R.; Santos, E.; Loza, E.; Carmona, L.; Pereira da Silva, J.A.
Abstract : Background: Several prediction algorithms/tools to estimate fracture risk probability have been developed in order to allow the optimization of treatment and prevention strategies. However, the existing algorithms differ in many relevant aspects and available reviews (1, 2) have a number of important limitations. Objectives: The aim of this review is to identify and synthesize the best available evidence on the accuracy of the currently available tools to predict the fracture risk in the general population. Methods: We systematically searched Pubmed MEDLINE, Embase and Cochrane databases up to 2014, using Mesh terms and open language. Two reviewers independently selected the articles and collected data from the studies by using ad hoc standard forms. A hand search was completed by reviewing the references of the included studies. A meta-analysis was performed using a random effects model.Methodological quality was assessed using the Quality Assessment Tool for Diagnostic Accuracy Studies (QUADAS) checklist. The primary outcome was the Area Under the Curve (AUC) and 95% confidence intervals (CI), obtained from Receiver Operating Characteristic (ROC) analysis. We excluded tools if they: a) had not been externally validated, b) were designed for specific disease populations. Results: Forty-five studies met inclusion criteria, corresponding to 13 different tools. Only three tools had been tested more than once in a population-based setting: FRAX® (26 studies in 9 countries), GARVAN (6 studies in 3 countries) and QFracture® (4 studies in the UK). Nineteen studies with these three tools were included in 10 meta-analysis (for hip or major osteoporotic fractures; men or women; with or without BMD). The results obtained for the 10 years hip fracture prediction are presented in Figure 1 . Conclusions: Most of the 13 tools are feasible in clinical practice and are of simple access and use. FRAX® has the largest number of externally validated and independent studies. The overall accuracy of the different tools is satisfactory (>0.70). Significant methodological limitations were observed in many studies, imposing caution on the comparison of the tools based solely on AUC. Several other aspects need also to be taken into consideration to select the best tool for a given objective and setting. References: Rubin KH, Friis-Holmberg T, Hermann AP, Abrahamsen B, Brixen K. Risk assessment tools to identify women with increased risk of osteoporotic fracture: complexity or simplicity? A systematic review. Journal of bone and mineral research: the official journal of the American Society for Bone and Mineral Research. 2013;28(8):1701-17. Nayak S, Edwards DL, Saleh AA, Greenspan SL. Performance of risk assessment instruments for predicting osteoporotic fracture risk: a systematic review. Osteoporosis international: a journal established as result of cooperation between the European Foundation for Osteoporosis and the National Osteoporosis Foundation of the USA. 2014;25(1):23-49. Disclosure of Interest: None declared